Konrad Hesse’s praktische Konkordanz as a Method of Balancing Constitutional Rights in the Lithuanian and Latvian Legal Systems - Šuspāns, Artūrs (Teisė, 2025)
This article addresses the question of whether Konrad Hesse’s method for resolving collisions of constitutional rights, named practical concordance, can be applicable in the Lithuanian and Latvian legal systems. The first part of the article introduces and compares two constitutional right conflict-resolving methods – the principle of practical concordance and the ad hoc balancing method. Further, the article analyses whether the principle of practical concordance is recognised and applied in the Lithuanian and Latvian legal systems. The article concludes with the thesis that the principle of practical concordance can be applied in the Lithuanian and Latvian legal systems, and that both legal systems have a similar and comparable understanding of the application of the principle of practical concordance.